A systematic review and meta-analysis comparing single port laparoscopic myomectomy with conventional laparoscopic myomectomy. (August 2019) - Lee, Dayong; Lee, Jung Ryeol; Suh, Chang Suk; Kim, Seok Hyun
Abstract: Objective: We systematically evaluated if there are any clinical differences in the safety and feasibility of single port laparoscopic myomectomy when compared to conventional laparoscopic myomectomy. Study Design: A meta-analysis and systematic review was conducted in accordance with the PRISMA statement. We searched different databases including Medline, Embase, Cochrane, and Google Scholar up to April 2018. Comparative studies as randomized controlled trials and prospective and retrospective cohort studies were included. Results: A meta-analysis was performed on the safety, feasibility, and potential benefits. Two randomized controlled trials and six cohort studies (2 prospective and 4 retrospective) were meta-analyzed to compare the surgical outcomes of 907 patients. Rates of minor complications were not different between the two groups [OR 1.33 (0.67, 2.63), I 2 = 0%]. Major complications requiring re-operation occurred in two cases in the single port group and in the conventional group respectively. There was no significant statistical difference between the groups. Conversion to laparotomy did not occur in either group, and the conversion rate from single port to the multi-port operation was 2.1% (6/288). The pain score one hour after operation was significantly lower in the single port group [MD -0.41 point (-0.63, -0.18), I 2 = 3.7%]. However, this difference was not observed at six and 24 h postoperatively. There was no difference in the operation time, estimated blood loss, or hemoglobin decrease between the two groups. Conclusion: A meta-analysis showed that single port laparoscopic myomectomy is comparable to conventional laparoscopic myomectomy in terms of safety and feasibility and more advantageous in terms of immediate postoperative pain. If performed based on the appropriate patient selection criteria including size and number of myoma, single port laparoscopic myomectomy can have similar surgical outcomes to those of conventional laparoscopic myomectomy. Further research and resources are required to identify whether single port laparoscopic myomectomy is more beneficial in terms of cosmetic results, patient satisfaction, and pregnancy outcomes.